1987
DOI: 10.1002/aic.690330316
|View full text |Cite
|
Sign up to set email alerts
|

Gas holdup and volumetric mass transfer coefficient in bubble columns with dilute alcohol solutions

Abstract: Applications of bubble columns in different fields of chemical industry and in diverse gas-liquid systems has shown that their behavior often depends very strongly on the nature of the liquid phase. The liquid phase in bioreactions and in coal liquefaction, which are important areas of bubble column use, can be simulated fairly well with dilute alcohol solutions (Schiigerl et al., 1977). However, the literature offers a limited quantity of the information on this subject. Schiigerl et al. investigated gas hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 6 publications
5
47
0
Order By: Relevance
“…Posarac et al used aliphatic alcohols (with concentrations of 0.5 and 1 vol.-% at a superficial gas velocity of 1-8 cm s -1 ) in a bubble column and considered the volumetric mass transfer coefficient and gas holdup [51]. They proved that an enhancement in the number of carbon atoms (in the straight chain of alcohol) and its concentration increase k L a.…”
Section: Gas-liquid Mass Transfermentioning
confidence: 97%
“…Posarac et al used aliphatic alcohols (with concentrations of 0.5 and 1 vol.-% at a superficial gas velocity of 1-8 cm s -1 ) in a bubble column and considered the volumetric mass transfer coefficient and gas holdup [51]. They proved that an enhancement in the number of carbon atoms (in the straight chain of alcohol) and its concentration increase k L a.…”
Section: Gas-liquid Mass Transfermentioning
confidence: 97%
“…It can be defined as the percentage by volume of the gas in the two or three phases mixture in the column (Shah et al [2]). The influence of gas velocity on gas holdup for alcohols aqueous solutions is reported by Posarac and Tekic [5]. They found that gas holdup value increase with increasing gas velocity and depend significantly on the type of alcohol added.…”
Section: Introductionmentioning
confidence: 94%
“…By using a large experimental data set, Syeda et al (2002) have developed a semi−empirical correlation for ε G prediction in both pure liquids and binary mixtures. Pošarac and Tekić (1987) proposed a reliable empirical correlation which enables the estimation of gas holdup in bubble columns operated with dilute alcohol solutions. A number of gas holdup correlations were summarized by Hikita et al (1980).…”
Section: Estimation Of Gas Holdupmentioning
confidence: 99%